Photo-induced copper-RDRP in continuous flow without external deoxygenation. Issue 32 (19th July 2019) - Marathianos, Arkadios; Liarou, Evelina; Anastasaki, Athina; Whitfield, Richard; Laurel, Matthew; Wemyss, Alan M.; Haddleton, David M.
Abstract : Photo-induced Cu-RDRP of acrylates in a continuous flow reactor without the need for deoxygenation or externally added reagents. Abstract : Photo-induced Cu-RDRP of acrylates in a continuous flow reactor without the need for deoxygenation or externally added reagents. Optimization of the catalyst concentration and the flow rate/residence time leads to well-defined polyacrylates with controlled molecular weights, excellent initiator efficiency, high end-group fidelity polymers and product uniformity. A multifunctional initiator was also used to demonstrate the versatility of the system.